2019
DOI: 10.21608/jpp.2019.48294
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Magnetization and Organic Acids on the Growth and Productivity of ‘Washington Navel Orange’ Trees under Irrigation with Salty Water

Abstract: The current investigation was executed to assess the effects of magnetization, which combines magnetized water (MW) and magnetic iron (150g tree -1 ), and organic acids (Humic acid at 150cm tree -1 ) As anti-salinity factors in mitigating the negative effects of salinity on growth, leaf mineral contents, yield and fruit properties of Washington Navel orange trees planted in sandy soil and watered with drip irrigation method (ECw of irrigation water = 4ds/m) in 2014 and 2015 under El-Behera governorate conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
1
3
1
Order By: Relevance
“…Magnetic iron at a concentration of 750 g.tree −1 achieved the highest values in comparison to those of other treatments. The stimulatory result of magnetic iron on fruit juice volume reported in this study is incompatible with El-Dengawy et al [ 40 ], who stated that magnetic iron treatments significantly increased fruit weight and volume of ‘Washington’ navel orange fruits when compared with that of untreated trees. The same applies to Ennab [ 6 ] and Mohamed et al [ 36 ] for mandarin trees.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Magnetic iron at a concentration of 750 g.tree −1 achieved the highest values in comparison to those of other treatments. The stimulatory result of magnetic iron on fruit juice volume reported in this study is incompatible with El-Dengawy et al [ 40 ], who stated that magnetic iron treatments significantly increased fruit weight and volume of ‘Washington’ navel orange fruits when compared with that of untreated trees. The same applies to Ennab [ 6 ] and Mohamed et al [ 36 ] for mandarin trees.…”
Section: Resultscontrasting
confidence: 99%
“…On the other hand, the lowest percentage of vitamin C in fruits was recorded when mandarin trees received no treatment (control). These results are supported with the previous study of El-Dengawy et al [ 40 ], who found that magnetic iron treatments significantly increased vitamin C in ‘Washington’ navel orange fruits. The increase in vitamin C (Ascorbic acid mg/100 mL of fruit juice) in fruit juice at harvest time might be due to the increase in weight of the fruit and the increase in the parameters of vegetative growth, such as shoot length and leaf area, caused by magnetic iron treatment; it also may be due to irrigation with magnetized water, causing a significant increase in the activities of the antioxidant enzymes over the control plants [ 48 ].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations